La Biblia de Lérida. Apuntes para un estudio arqueológico - Suárez González, Ana (Estudios humanísticos. Geografía, historia y arte, 1998)
This work is centered on the analysis of a manuscript of great interest: the Bible of Lérida (12th century): number of pages, the size, mounting, the notebook structure, page size, inks, type of writing and the binding. These are some of the first results of a study that is taking place at the moment.